The Room as Metaphor: Next-of-Kin's Experiences in End-of-Life Care. (18th November 2015) - Werkander Harstäde, Carina; Roxberg, Åsa
Abstract : The "room" in end-of-life is a phenomenon that needs deeper understanding as it is a dimension that shows how health and suffering are shaped. Research on the concept of room was chosen as theoretical foundation in this study in order to reach a profound understanding of the next-of-kin's "room" in end-of-life care. Lassenius's hermeneutic interpretation in metaphorical language was used as an deductive-inductive approach to the empirical data. The data material comprised 33 interviews with next-of-kin about their experiences of end-of-life care when being close to a relative dying from a cancer disease. The analysis of the data formed four cases: the Standby, the Asylum, the Wall, and the Place. These cases lend their voices to the experiences of the next-of-kin in the study. The findings of this study explain and may well assist nurses to understand the experiences of being next-of-kin in end-of-life care as forming a room of rest from the suffering, a room of controlling the suffering, a room of hiding from the suffering, and a room of belonging.